LEARNING ANALYTICS–ENABLED MULTIMEDIA INSTRUCTION AND ITS IMPACT ON ENGLISH LANGUAGE SKILL DEVELOPMENT IN ENGINEERING HIGHER EDUCATION: AN EMPIRICAL INVESTIGATION - N. SIVAKAMI; Dr.S.GUNASEKARAN (The Bioscan, 2026)
The integration of learning analytics and multimedia instruction has transformed contemporary higher education, yet its empirical impact on English language skill development in engineering contexts remains underexplored. This study investigates the effectiveness of learning analytics–enabled multimedia instruction in enhancing English language skills among undergraduate engineering students. Adopting a quasi-experimental pre-test–post-test control group design, the research was conducted over a twelve-week intervention period involving structured multimedia modules integrated within a Learning Management System (LMS). The instructional framework incorporated interactive videos, digital writing tasks, automated quizzes, peer-feedback platforms, and analytics dashboards to monitor learner engagement, participation patterns, and performance trajectories.